Volume 6: Structures and Dynamics, Parts a and B 2011
DOI: 10.1115/gt2011-45932
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Blade Row Interactions in a Low Pressure Ratio Centrifugal Compressor Stage With a Vaned Diffuser

Abstract: Previous experimental and CFD investigation of a GE Oil and Gas centrifugal compressor stage with a vaneless diffuser revealed a complex excitation mechanism caused by an aero-acoustic interaction between three blade rows. In stages with vaned diffusers, additional sources of aeromechanical excitation on the impeller can be expected. This unsteady CFD investigation is a follow-up from the previous vaneless diffuser study to identify any additional sources of excitation that arise in the presence of a vaned dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Previous validations and modeling experiences with TACOMA on centrifugal compressor stages can be found in [16], [17], [18] , [1] and [19] .…”
Section: Numerical Approachmentioning
confidence: 99%
“…Previous validations and modeling experiences with TACOMA on centrifugal compressor stages can be found in [16], [17], [18] , [1] and [19] .…”
Section: Numerical Approachmentioning
confidence: 99%
“…This last contribution emanates from the cooling requirements of the rotor disks under the main flow passage that induce additional losses by a blowing process of the cavity flow in the main annulus. The understanding of these effects is important since potential for further improvement in the turbomachine are still expected with the potential unsteady effects [4], mixing processes due to non-uniformities, intermittent wakes [5], and interaction between the different blade rows [6]. The interactions of wakes of upstream rows can have a strong impact on the stability and turbulent characteristic of the downstream blades boundary layers and endwall losses as experimentally studied by Steurer et al [7] using upstream moving bars to generate wakes on a low-pressure turbine cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Their study showed the efficiency of the TT method in terms of computation costs and accuracy. Ramakrishnan et al (2011) presented unsteady CFD results on a compressor stage equipped with a vaned diffuser. In this paper, the authors identified the aerodynamic modes in the radial gap between the impeller and the vaned diffuser only through numerical simulations, according to the Tyler-Sofrin theory (1961).…”
Section: Introductionmentioning
confidence: 99%